Proceedings of the XII International Symposium on Biological Control of Weeds, La Grande Motte, France, 22-27 April, 2007 2008
DOI: 10.1079/9781845935061.0091
|View full text |Cite
|
Sign up to set email alerts
|

Fortieth anniversary review of the CSIRO European Laboratory: does native range research provide good return on investment?

Abstract: CSIRO established its first overseas research laboratory on biological control at Montpellier in late 1966 to start a programme on skeleton weed, Chondrilla juncea L.). The laboratory was set up to develop the science to underpin effective biological control, by parallel studies in the native and introduced range of Australia's pests. Since establishment within a French research agency (CNRS), the facility moved in 1994 from rented facilities into a purpose-built CSIRO-owned facility, with support from Austral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This was Australia's first investment in an overseas facility to support weed biological control research in the native range of the target weed. CSIRO subsequently rented separate premises before building new facilities in the early 1990s (Sheppard et al 2008). The success of the skeleton weed program (Burdon et al 1981;Cullen 1978;Cullen et al 1973), the fact that it was achieved by the deliberate introduction of a plant pathogen, the biotrophic rust (Puccinia chondrillina) Bubàk & Syd., and the demonstrated economic benefits (Marsden et al 1980) Montpellier facility, whereas there were significant contributions from New South Wales, the Northern Territory and Tasmania.…”
Section: The History Of Biological Control In Australiamentioning
confidence: 99%
“…This was Australia's first investment in an overseas facility to support weed biological control research in the native range of the target weed. CSIRO subsequently rented separate premises before building new facilities in the early 1990s (Sheppard et al 2008). The success of the skeleton weed program (Burdon et al 1981;Cullen 1978;Cullen et al 1973), the fact that it was achieved by the deliberate introduction of a plant pathogen, the biotrophic rust (Puccinia chondrillina) Bubàk & Syd., and the demonstrated economic benefits (Marsden et al 1980) Montpellier facility, whereas there were significant contributions from New South Wales, the Northern Territory and Tasmania.…”
Section: The History Of Biological Control In Australiamentioning
confidence: 99%
“…Simulation modelling using data from the natural range in addition to quarantine studies can assist in predicting non-target impacts [85]. The cost-effectiveness of native range research for CSIRO has been clearly demonstrated [86].…”
Section: Assessment Of Biological Control Safetymentioning
confidence: 99%
“…USDA or CABI). CSIRO continues to maintain two overseas facilities, at Montpellier in France (Sheppard et al, 2008) (used regularly by Victorian Department of Primary Industries (VicDPI)) and at Veracruz in Mexico, from which 16 agents have been released in Australia against four weed targets. A recent study of the economic returns on investment of Australia's funding its own overseas laboratory in France for 40 years estimated a conservative return on investment of 27:1 in additional to high science impact for the discipline (Sheppard et al, 2008).…”
Section: Overseas Field Stations and Explorationmentioning
confidence: 99%